Wolbachia -mediated viral transmission enhancement in insect vectors - Ying Wang; Shunkang Zhou; Shuwei Li; Lizhi Wang; Shupei Ai; Jilei Huang; Xin Yi; Kan Zhuo; Guohui Zhou; Xin Yang; Tong Zhang (Proceedings of the National Academy of Sciences, 2026)
The white-backed planthopper ( Sogatella furcifera ) serves as the vector for the southern rice black-streaked dwarf virus (SRBSDV), with varying transmission efficiencies across populations. This research identifies Wolbachia , a common insect symbiont, as a key facilitator in breaching the salivary gland barrier for SRBSDV, revealing a mechanism by which the virus exploits an insect symbiont for transmission. Through field and laboratory investigations, it was observed that high-transmission (HT) planthopper populations contained high levels of Wolbachia , while low-transmission (LT) populations had minimal titers. Experiments involving thoracic injections confirmed Wolbachia ’s specific role in infiltrating salivary glands, as SRBSDV was unable to colonize glands in Wolbachia -depleted insects despite being present systemically. Ultrastructural analysis showed Wolbachia enveloping SRBSDV particles within gland cells, further supported by molecular assays indicating a direct interaction between Wolbachia surface protein (WSP) and viral P8 capsid protein. Disruption of this interaction using anti-WSP antibodies reduced salivary gland viral load and transmission rates, underscoring its functional importance. These results contrast with Wolbachia ’s antiviral effects in mosquitoes, highlighting a context-dependent “hitchhiking” strategy for viral dissemination. The WSP–P8 interaction presents a specific target for inhibiting SRBSDV transmission without resorting to pesticides, proposing a symbiont-informed approach as a sustainable strategy against rice viral diseases.